2019
DOI: 10.3390/geosciences9090383
|View full text |Cite
|
Sign up to set email alerts
|

Dependence Models of Borehole Expansion on Explosive Charge in Spherical Cavity Blasting

Abstract: In geotechnical practice, it is often necessary to improve the properties of soil and rock in which different structures are built. For this purpose, spherical cavity blasting can be applied to expand the borehole. Such expansion may incorporate various constructive elements such as anchors and thus stabilize the slope. The paper presents the method for determining the increased volume, expansion, and deepening of the borehole as a result of spherical cavity blasting. In addition, mathematical models describin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 10 publications
0
24
0
Order By: Relevance
“…Other than performed research from 2014 to 2016 [15], and researche in Težak, D. 2018 [6] and Težak, D. et al 2019 [1], there are a couple of similar methods found in literature.…”
Section: Previous Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…Other than performed research from 2014 to 2016 [15], and researche in Težak, D. 2018 [6] and Težak, D. et al 2019 [1], there are a couple of similar methods found in literature.…”
Section: Previous Researchmentioning
confidence: 99%
“…The area of interest was blasted in soft rock in order to create spherical volume cavities using different types and masses of explosive. Collection of all the field data and the innovative approach in data processing were published in Težak D. et al, 2019 [1].…”
Section: Extended Power Modelmentioning
confidence: 99%
See 3 more Smart Citations